Ax+Fy=Kforx

Simple and best practice solution for Ax+Fy=Kforx equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Ax+Fy=Kforx equation:


Simplifying
Ax + Fy = Kforx

Solving
xA + yF = forxK

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1forxK' to each side of the equation.
xA + -1forxK + yF = forxK + -1forxK

Reorder the terms:
-1forxK + xA + yF = forxK + -1forxK

Combine like terms: forxK + -1forxK = 0
-1forxK + xA + yF = 0

Add '-1yF' to each side of the equation.
-1forxK + xA + yF + -1yF = 0 + -1yF

Combine like terms: yF + -1yF = 0
-1forxK + xA + 0 = 0 + -1yF
-1forxK + xA = 0 + -1yF
Remove the zero:
-1forxK + xA = -1yF

Combine like terms: -1yF + yF = 0
-1forxK + xA + yF = 0

The solution to this equation could not be determined.

See similar equations:

| 1.25=217+x/(13.2-X)(32.8-X) | | -12n+6=-10n-2 | | 2(4a-7)+a=76 | | -37-(-43)=x/6 | | 2(4c-1)-6=3c+7 | | -7(t+1)=14 | | -7(t+1)=4 | | 1/2(18x+2)=3(3x-2)-3(x-7) | | 1/2(p+6)=7/2(3-p) | | 3x^2+(k-1)x-2=0 | | 27-19=4(x-6) | | -7x+1=9 | | 30+5y-12=17y-9-3y | | x+23+4x=-22-4x-27 | | -x(x-2)(x+2)(x+2)=0 | | b^12*b^10= | | -0.4x^2+2.2x+4.7=0 | | w^6*w^8= | | 5q^2-2bq-3=0 | | -4x+1=33 | | 2m/5+4=-10/9-3 | | P(2)-10P+22=0 | | 3(z-4)+6= | | -11/7=z-2/3 | | 2log(x-3)-log(x+1)=2 | | k*k^12= | | 4x^2+7x=6 | | a^4-6a^2+5=0 | | 6+2(1+2x)=29-3x | | 2x-7(3-2x)=11 | | 2((1.5+2)+(1.5+3))=16 | | 154=4x^2+26x+40 |

Equations solver categories